Trajectories into famine: observations of patterns and implications for prevention - Daniel Maxwell; Matthew Day; Merry Fitzpatrick; Paul Howe; Peter Hailey; Anu Atre; Alex de Waal (Food Policy, 2026)

Seeing famines: An exploration of the spatial dimensions of severe hunger crises - Paul Howe; Theo Anastopoulo; Christopher Newton (Global Food Security, 2025)

A nautiloid with ventral bitemarks from the Charmouth Mudstone Formation (Lower Jurassic) near Lyme Regis, Dorset, UK - Paul Davis; Paddy Howe; Chris Paul; Heather Salmon (Proceedings of the Geologists' Association, 2023)

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Analysis of surfactant-associated bacteria in the sea surface microlayer using deoxyribonucleic acid sequencing and synthetic aperture radar - Georgia Parks; Cayla W. Dean; John A. Kluge; Alexander V. Soloviev; Mahmood Shivji; Aurelien Tartar; Kathryn L. Howe; Susanne Lehner; Egbert Schwarz; Hui Shen; William Perrie; Paul Schuler (International Journal of Remote Sensing, 2020)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Further human evidence for striatal dopamine release induced by administration of ∆9-tetrahydrocannabinol (THC): selectivity to limbic striatum - Matthijs G. Bossong; Mitul A. Mehta; Bart N. M. van Berckel; Oliver D. Howes; René S. Kahn; Paul R. A. Stokes (Psychopharmacology, 2015)

Spawning and early ontogenesis in channel bull blenny Cottoperca gobio (Notothenioidei, Perciformes) caught off the Falkland Islands and maintained in captivity - Alexander Arkhipkin; Elena Boucher; Paul Nicholas Howes (Polar Biology, 2015)

The relationship between reward and punishment processing and the 5-HT1A receptor as shown by PET - Paul Faulkner; Sudhakar Selvaraj; Alex Pine; Oliver D. Howes; Jonathan P. Roiser (Psychopharmacology, 2014)

Spawning, egg development and early ontogenesis in rock cod Patagonotothen ramsayi (Regan, 1913) caught on the Patagonian Shelf and maintained in captivity - Alexander Arkhipkin; Elena Jurgens; Paul Nicholas Howes (Polar Biology, 2013)

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Margarita D. Tsiros; Alison M. Coates; Peter R. C. Howe; Paul N. Grimshaw; Jeff Walkley; Anthony Shield; Richard Mallows; Andrew P. Hills; Masaharu Kagawa; Sarah Shultz; Jonathan D. Buckley (European Journal of Applied Physiology, 2013)

Glycemic index, glycemic load, and pancreatic cancer risk (Canada) - Stephanie A. N. Silvera; Thomas E. Rohan; Meera Jain; Paul D. Terry; Geoffrey R. Howe; Anthony B. Miller (Cancer Causes & Control, 2005)

DNA extraction from plants: The use of pectinase - Steven H. Rogstad; Brian Keane; Carolyn Howes Keiffer; Fred Hebard; Paul Sisco (Plant Molecular Biology Reporter, 2001)

A review of boron effects in the environment - Paul D. Howe (Biological Trace Element Research, 1998)